Don Troiani's Gettysburg : 36 Masterful Paintings and Riveting History of the Civil War's Epic Battle /: 36 Masterful Paintings and Riveting History of the Civil War's Epic Battle. (2019) - Troiani, Don; Huntington, Tom
No abstract available